PENGARUH PENAMBAHAN AGREGAT LIMBAH BOTOL KACADAN ABU SERABUT KELAPA TERHADAP KARAKTERISTIK BATU BATA - Miftahul Husnah; Abdul Halim Daulay; Siska Siska (JISTech (Journal of Islamic Science and Technology), 2022)
This study aims to (i) determine the effect of adding glass bottle waste aggregate and coconut fiber ash to the characteristics of the bricks and (ii) to determine the composition of mixing glass bottle waste aggregate and coconut fiber ash so that bricks with optimal characteristics are produced. The materials used in this study were glass powder, coconut fiber ash, and clay with a composition of glass powder, coconut fiber ash, and clay 0%:0%:100%, 5%:5%: 90%, 10% :10%:80%, 15%:15%:70%, and 20%:20%:60% with a FAS of 0.5. The process of making bricks is done manually. Characterizations carried out include: compressive strength, water absorption, and density. The addition of glass bottle waste aggregate and coconut fiber ash as a substitute for clay has an effect on the characteristics of the bricks. As the amount of glass powder and coconut fiber ash increases, the compressive strength value tends to decrease, the water absorption value tends to increase, and the density value tends to decrease. The compressive strength values in all compositions of mixing glass powder, coconut fiber ash, and clay still do not meet the SNI 15-2094-2000 standard. The value of water absorption at the composition of 5%:5%: 90% and 10%:10%:80% already meets the standards of SNI 15-2094-2000. Density values in all compositions have met the standards of SNI 15-2094-2000, except for the composition 15%: 15%: 70%. %:10%:80%.